Regression and Underrepresentation: An Analysis of the Decline in African American Fortune 500 CEO in the 21st Century - Dowe Jr., Michael (2019)
For Corporate America, diversity has been an issue that seems to be non-existent especially when looking at C-level suite executives. From the outside, diversity in Fortune 500 CEO positions is an issue that initially appeared to be trending in a positive direction in the 21st century. However, African Americans Fortune 500 CEOs numbers have dwindled to the current 3 reigning African American CEOS, down from a high of 6 in 2012. This paper investigates the declining rate of African American Fortune 500 CEOS, their tenure, and their turnover rates through a qualitative methods and case study approach, analyzing trends among the succession of African American CEOS. It demonstrates that declining rates are correlated with theories such as Glass Cliffs, Bold Moves, Glass Ceilings, and the Savior Effect and raises the question of whether diversity in Corporate America is going to continue regressing in the 21st century.